Aliens in Egyptian Mediterranean waters. A check-list of Erythrean fish with new records - HALIM, Y.; RIZKALLA, S. (Mediterranean Marine Science, 2011)
The historical role of the Suez Canal as a pathway for migrations between the Red sea and the Mediterranean is recalled. A check-list of 42 immigrant Erythrean fish in Egyptian Mediterranean waters is given. The list comprises four new records. 17 of the immigrant species are commercially exploited, whereas 15 are known from single records. While the Erythrean fish as invasive species are beneficial to local fisheries, in our view, they do not have an important impact upon the ecosystem.